The Influence of Hard Skills, Soft Skills, Spiritual Skills and Organizational Commitment on Professionalism - Rosyida Nurhamidah; Istatin; Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine and explain the influence of Hard Skills, Soft Skills, Spiritual Skills, and Organizational Commitment on the professionalism of employees at Puskesmas Grogol Sukoharjo. This research uses a descriptive quantitative method. The quantitative data for this research consists of respondents' opinions in the questionnaire. This research was conducted at Puskesmas Grogol, Sukoharjo Regency, located at Jalan Raya Grogol No 47 Grogol, Sukoharjo Regency, in December 2024 - January 2025. The location was chosen with the consideration that the Grogol Health Center, Sukoharjo Regency, had not been used for the same research and the suboptimal performance of the staff. The population of this study consists of 120 employees of the Grogol Community Health Center, Sukoharjo Regency. The sample taken for this study is a portion of the employees of the Grogol Community Health Center, Sukoharjo Regency, totaling 36 employees. In this study, the sampling technique used is non-probability sampling with the technique taken being simple random sampling with a simple proportion approach, namely 30% of the total population. The data analysis technique uses the Multiple Linear Analysis method. Based on the research results, there is an influence of Hard Skills, Soft Skills, Spiritual Skills, and Organizational Commitment on the Professionalism of Grogol Sukoharjo Health Center Employees. It can be concluded that based on the calculations, an adjusted R square value of 0.619 was obtained. This means that the variables of hard skills, soft skills, spiritual skills, and organizational commitment contribute to professionalism by 61.9%, while the remaining 38.1% is explained by other variables not included in this study. Keywords: Professionalism, Hard Skills, Soft Skills, Spiritual Skills, Organizational Commitment, Puskesmas Employees.